Factors that Influence Womens Economic Participation in Mexico - Rafael Garduño-Rivera (Centro de Investigación y Docencia Económicas, A.C., 2013)
This paper analyses womens economic participation (wep) in Mexico. The hypothesis is that the regional disparities of womens participation are based on education, industrialization, urbanization and other non-observed factors. The question that this study addresses is: What regional factors influence womens participation and cause disparities in their participation across municipalities? Additionally, this paper measures the progress and the current state of wep during the last decades, and the evolution of the differences across regions. The study tests an econometric model about the influence of various socio-economic factors on wep. The results show that the main barriers to female participation are the lack of higher education and the absence of diverse work possibilities in industries such as manufacturing and hoteling. Other factors mentioned in the literature that also affect wep are the number of children per household and poverty in each municipality. Therefore, these variables contribute to increasing wep and should be the focus of any attempt to increase their labor force participation in the formal sector.